Revisiting the Trust of Online Services Middle Age M-Health Users in Indonesia - Endah Nawangsih; Siti Marliah Tambunan; Dian Kemala Putri (UPT Publikasi Ilmiah (Universitas Islam Bandung), 2023)
Abstract. The purpose of this research is to test the effects of social support and online trust behavior on the adherence in 212 middle-aged m-Health users in Indonesia. The data was obtained incidentally by distributing questionnaires to middle-aged m-Health users in Indonesia. The measuring instruments used are social support, online trust behavior, and the Health Care Climate Questionnaire (HCCQ). The survey method is analyzed using Structural Equation Modeling (SEM) with the Linear Structural Relations (LISREL) program version 8.7. The results show a direct effect between social support and the adherence of middle-aged m-Health users, a direct effect of online trust behavior on the adherence of middle-aged m-Health users, and an indirect effect of social support on adherence mediated by online trust behavior in middle-aged m-Health users. The discussion of the results is described in the article.